2023
DOI: 10.3390/jfb14030147
|View full text |Cite
|
Sign up to set email alerts
|

Degassing a Decellularized Scaffold Enhances Wound Healing and Reduces Fibrosis during Tracheal Defect Reconstruction: A Preliminary Animal Study

Abstract: Few efforts have been made regarding the optimization of porcine small intestinal submucosa (SIS) to improve its biocompatibility. This study aims to evaluate the effect of SIS degassing on the promotion of cell attachment and wound healing. The degassed SIS was evaluated in vitro and in vivo, compared with the nondegassed SIS control. In the cell sheet reattachment model, the reattached cell sheet coverage was significantly higher in the degassed SIS group than in the nondegassed group. Cell sheet viability w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…SIS grafts encouraged the regeneration of airway mucosa at the implant site, and the majority of SIS implants degraded within a month of surgery [ 145 ]. A recent survey reported that SIS mesh treated with a vacuum system exhibited superior cell attachment and viability compared to the control group [ 146 ]. Moreover, the in vivo findings indicated that the repair of tracheal defects using degassed SIS mesh demonstrated improved healing, fibrosis, and luminal stenosis in contrast to the control group employing ungassed SIS.…”
Section: Tissue Repair Using Functional Sismentioning
confidence: 99%
“…SIS grafts encouraged the regeneration of airway mucosa at the implant site, and the majority of SIS implants degraded within a month of surgery [ 145 ]. A recent survey reported that SIS mesh treated with a vacuum system exhibited superior cell attachment and viability compared to the control group [ 146 ]. Moreover, the in vivo findings indicated that the repair of tracheal defects using degassed SIS mesh demonstrated improved healing, fibrosis, and luminal stenosis in contrast to the control group employing ungassed SIS.…”
Section: Tissue Repair Using Functional Sismentioning
confidence: 99%